Experimental research on brine crystallization mechanism in solution mining for salt cavern energy storage. (30th November 2022) - Wei, Xinxing; Liu, Yuanxi; Shi, Xilin; Li, Yinping; Ma, Hongling; Hou, Bingren; Shangguan, Shuantong; Li, Zhiqiang; Niu, Yaohui
Abstract: During construction of deep salt cavern energy storage, the debrining string is often blocked by salt crystals. The accident increases the construction time and its cost. In this paper, a salt cavern gas storage project in Hebei Ningjin, China, is used as the basis to collect some salt samples from a depth of 2900 m for crystallization tests. The crystallization of the salt rock from different strata is studied, in different the amount of freshwater and at different temperatures. The effect of a temperature difference on solubility is analyzed by clustering. The solubility of salt rock at high temperature is analyzed by gray system prediction theory. A fitting relationship between temperature and solubility is established. A salt crystallization weight model is established by a hierarchical analysis model to portray the salt crystallization quantitatively. The results shows that the salt rock crystal purity of the salt layer is high, its solubility curve is similar to the pure NaCl dissolution curve. The temperature difference and the amount of fresh water supplied are the key factors affecting salt crystallization. By the model results and experimental data, salt crystallization anti-blocking measures are analyzed. A salt crystallization anti-blocking method is proposed for the engineering practice of salt cavern mining. Highlights: Verify the temperature difference is a key factor that influences the salt crystallization by a coupling model. A gray system model is established to analyze the temperature-solubility relationship. A full-factor evaluation model is established to analyze salt crystallization influence factors. Proposed the debrining string unblocking process flow chart by the models and the data.